Complaints Of Musculoskeletal Disorders (MSDs) In Terms Of Work Posture And Work Period In The Polishing Section Of Terazzo Craftsmen In The Sodo Village, Pakel District, Tulungagung Regency - Pratiwi, Ariesta Puspa; Wardani, Ratna (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2022)
Musculoskeletal Disorders are disorders related to muscle tissue, tendons, ligaments, and nerves. Factors that can lead to the formation of complaints of the musculoskeletal system are an odd form of work posture and a long work period. The purpose of this study was to determine the effect of work posture and work period on complaints of musculoskeletal disorders in terazzo craftsmen polishing workers in Sodo Village, Pakel District, Tulungagung Regency. This research is a quantitative study, with a cross sectional approach. The population is 45 workers in the polishing section of craftsmen. A sample of 40 respondents with the sampling technique using simple random sampling technique. This study uses the REBA observation sheet to assess work posture, interviews to determine work period, and the NBM questionnaire sheet to assess complaints of musculoskeletal disorders. Data analysis technique using multiple linear regression test. The result of multiple linear regression tests show that the proportion of the effect of work posture and work period is 45% on complaints of musculoskeletal disorders. Variable work posture had an effect on complaints of musculoskeletal disorders with a p value of 0,042. Work period variable also affects musculoskeletal disorders complaints with a p value of 0,001. To reduce complaints of musculoskeletal disorders, workers are advised to learn about the dangers of musculoskeletal disorders and how to overcome them, rest for a few minutes when the body begins to feel muscle fatigue, and business owners of terazzo craftsmen are advised to provide training to workers about the dangers of musculoskeletal disorders and how to overcome them, collaborating with health workers, providing ergonomic work facilities so as to avoid awkward postures.